'I'm gonna use this White face!': missteps of becoming a 'race'-cognizant White scholar. Issue 2 (3rd July 2019) - Rea Preston, Lauren
ABSTRACT: This story begins with the assumption that I, the White female researcher, would elicit 'better' data from White participants. I told my Black female professor, 'I'm gonna use this White face!' This became a metaphor to describe my entry into the site and the various interactions that took place there. I conclude that the way that my racial identity and that of the participants played into the study was incredibly complicated, multi-faceted, and not entirely predictable. The significance of my experience is not just about 'race'-matching in research, or racial identity, but also about how researchers theorise about 'race' and the level of 'race'-consciousness of the participants, as well as the methods they choose to do this work. This experience can inform other novice White researchers as they traverse the murky waters of simultaneously learning to do research and developing in 'race' cognisance.